Oral bowel cleansers and ischemic colitis risk: A real-world disproportionality analysis - Min Luo; Wenyu Li; Xuehong Wang; Yuqian Zhou (PLoS ONE, 2025)
Background Ischemic colitis (IC) is a serious but underrecognized complication potentially associated with bowel preparation. While previous studies have reported sporadic cases, the true frequency and drug-specific associations remain unclear. This study evaluates the association between oral bowel cleansers and IC using real-world pharmacovigilance data. Methods We conducted a disproportionality analysis using 20 years of data (2004–2024) from the FDA Adverse Event Reporting System (FAERS). IC cases linked to bisacodyl, polyethylene glycol (PEG), and oral sulfate solution (OSS) were identified. Multivariate logistic regression was applied to explore factors associated with IC and serious clinical outcomes. Results Among 43,958 adverse event reports related to bowel cleansers, 75 cases of IC were identified. Bisacodyl showed the strongest disproportionality signal for IC (reporting odds ratio (ROR) = 237.25), with a reporting proportion of 7.9%, followed by PEG (ROR = 2.18) and OSS (ROR = 3.64). Older age (≥70 years) and cardiovascular comorbidities were associated with more severe outcomes, such as hospitalization and death. Notably, reports of IC associated with PEG included six fatal and three life-threatening events. Conclusions To our knowledge, this is one of the largest pharmacovigilance analyses exploring ischemic colitis associated with bowel preparation agents. The findings raise concerns about the presumed safety of PEG and reveal a strong disproportionality signal for bisacodyl. These results highlight the need for individualized bowel preparation strategies, especially in elderly patients with comorbidities.